2010
DOI: 10.1111/j.1365-2052.2009.02016.x
|View full text |Cite
|
Sign up to set email alerts
|

A genome‐wide scan for signatures of recent selection in Holstein cattle

Abstract: The data from the newly available 50 K SNP chip was used for tagging the genome-wide footprints of positive selection in Holstein-Friesian cattle. For this purpose, we employed the recently described Extended Haplotype Homozygosity test, which detects selection by measuring the characteristics of haplotypes within a single population. To assess formally the significance of these results, we compared the combination of frequency and the Relative Extended Haplotype Homozygosity value of each core haplotype with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
180
3
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(202 citation statements)
references
References 65 publications
(117 reference statements)
17
180
3
1
Order By: Relevance
“…Within the remaining 38 intervals with a high proportion of Chief alleles in the current population of Australian Holsteins, we detected two genes, ARL4 and BMP4 (Fig. 2 A and B), that had been identified previously as candidate genes for QTL (21,22). Other functional candidates are given in Table 2.…”
mentioning
confidence: 74%
“…Within the remaining 38 intervals with a high proportion of Chief alleles in the current population of Australian Holsteins, we detected two genes, ARL4 and BMP4 (Fig. 2 A and B), that had been identified previously as candidate genes for QTL (21,22). Other functional candidates are given in Table 2.…”
mentioning
confidence: 74%
“…Therefore, the long runs of homozygosity observed in these regions are unlikely to be due to low recombination rates, but rather reflect selection pressures. Qanbari et al (2010) used SNPs of the Illumina Bovine SNP50 BeadChip and the REHH test to evaluate LD and the decay of haplotype homozygosity in some candidate regions harboring major genes related to milk production and quality in Holstein-Friesian cattle. In general, the authors found high values of LD and slow decay of haplotype homozygosity, indicating the validity of the approach for the identification of selection signatures.…”
Section: Resultsmentioning
confidence: 99%
“…The positive correlation of 0.34 between the two approaches demonstrated that the LRH test was able to detect haplotypes that suffered significant and recent changes in their frequency, indicating signatures of selection. Using EHH statistics to identify genome-wide selection signatures in Holstein-Friesian cattle, Qanbari et al (2010) found 161 regions (P < 0.01) that showed signs of recent positive selection. The larger number of regions indicative of positive selection identified by these authors, who used an SNP chip of the same density and the same significance criteria for the REHH test as in the present study, suggests more diverse (for different economically important traits) and intense selection in dairy cattle when compared with Quarter Horse racing, one of the most recently domesticated large animal species (Aberle and Distl, 2004).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…in Linkage Disequilibrium; LD) with an unknown causal variant and, in consequence, the study of such markers in a particular region of the genome can highlight the presence of polymorphisms influencing traits or diseases. In cattle breeds, the detection of such genetic differences is particularly interesting due to the strong artificial selection they have been subjected over the last 60 years (Qanbari et al 2010). Many genome-wide association studies (GWAS) identified associations between markers and productive or functional traits in dairy cattle breeds .…”
Section: Introductionmentioning
confidence: 99%